Divergent effects of cerium oxide nanoparticles alone and in combination with cadmium on nutrient acquisition and the growth of maize (Zea mays) - Ayub, Muhammad Ashar; Rehman, Muhammad Zia ur; Ahmad, Hamaad Raza; Rico, Cyren M.; Abbasi, Ghulam Hassan; Umar, Wajid; Wright, Alan L.; Nadeem, Muhammad; Fox, John-Paul; Rossi, Lorenzo (Frontiers in Plant Science, 2023)
The increasing use of cerium nanoparticles (CeO2-NPs) has made its influx in agroecosystems imminent via air and soil deposition or via untreated wastewater irrigation. Another major pollutant associated with anthropogenic activities is Cd which has adverse effects on plants, animals, and humans. The major source of Cd and Ce metals’ influx in the human food chain is through contaminated food consumption, making it an alarming issue, thus there is a need to understand factors that can reduce potential damage of these heavy metals. The present investigation was conducted to evaluate the effect of CeO2-10 nm sized-NPs and Cd (alone and in combination) on Zea mays growth. A pot experiment (in sand) was conducted to check the effect of 0, 200, 400, 600, 1000 and 2000 mg CeO2-10 nm-NPs kg-1 dry sand alone and in combination with 0 and 0.5 mg Cd kg-1 dry sand on maize seedlings grown under a partially controlled greenhouse environment, making a total of 12 treatments applied in 4 replicates under factorial design. The maize seedling biomass, shoot and root growth, nutrient content, and root anatomy were observed. These nanoparticles (10 nm size) were toxic for plant biomass (shoot and root dry weight) and growth with 2000 ppm being the most toxic in Cd-0 sets, while in Cd-0.5 sets, NPs applied at 1000 ppm reversed Cd toxicity compared to contaminated (CC). The CeO2-NPs also affected Cd translocation and variable Ce uptake was observed in the presence of Cd compared to non-Cd applied sets. The applied CeO2-NPs were also partially controlling root and shoot elemental contents (micronutrients like B, Mn, Ni, Cu, Zn, Mo, Fe and elements Co, Si) and affected root anatomy.